Organismal Function Enhancement through Biomaterial Intervention - Fengchao Tian; Yuemin Zhou; Zaiqiang Ma; Ruikang Tang; Xiaoyu Wang (Nanomaterials, 2024)
Living organisms in nature, such as magnetotactic bacteria and eggs, generate various organic–inorganic hybrid materials, providing unique functionalities. Inspired by such natural hybrid materials, researchers can reasonably integrate biomaterials with living organisms either internally or externally to enhance their inherent capabilities and generate new functionalities. Currently, the approaches to enhancing organismal function through biomaterial intervention have undergone rapid development, progressing from the cellular level to the subcellular or multicellular level. In this review, we will concentrate on three key strategies related to biomaterial-guided bioenhancement, including biointerface engineering, artificial organelles, and 3D multicellular immune niches. For biointerface engineering, excess of amino acid residues on the surfaces of cells or viruses enables the assembly of materials to form versatile artificial shells, facilitating vaccine engineering and biological camouflage. Artificial organelles refer to artificial subcellular reactors made of biomaterials that persist in the cytoplasm, which imparts cells with on-demand regulatory ability. Moreover, macroscale biomaterials with spatiotemporal regulation characters enable the local recruitment and aggregation of cells, denoting multicellular niche to enhance crosstalk between cells and antigens. Collectively, harnessing the programmable chemical and biological attributes of biomaterials for organismal function enhancement shows significant potential in forthcoming biomedical applications.